In Vitro Studies on the Fibrinolytic, Thrombolytic and Fibrinogenolytic Properties of a Tissue Plasminogen Activator from Guinea Pig Keratocytes - Electricwala, A; Ling, R J; Sutton, P M; Griffiths, B; Riley, P A; Atkinson, T (Thrombosis and Haemostasis, 1985)
The fibrinolytic and thrombolytic properties of a tissue plasminogen activator (tPA) purified from the conditioned medium of an established guinea pig keratocyte (GPK) cell line were investigated in in vitro systems and compared with urokinase. Using the fibrin clot lysis assay, GPK activator appears to be similar to human melanoma tPA and not to human urokinase. GPK activator also caused negligible fibrinogen breakdown, when incubated with human plasma at 37° C over 23 hr. Urokinase on the other hand caused significant fibrinogenolysis, under similar conditions. Comparison of the lysis of plasma clots by GPK activator and human urokinase have shown that GPK activator was a much more effective fibrinolytic agent than urokinase, especially at lower concentrations (<50 IU/ml). Studies on the thrombolytic effect of GPK activator on the lysis of aged and cross-linked whole human blood clots and plasma clots hanging in artificially circulating human plasma suggest that GPK activator can lyse both these types of clots equally well. The lysis is dose dependent, attaining complete lysis within 3–6 hr with the concentration of GPK activator in the range of 1–5 μg/ml plasma. It is concluded that GPK activator has a higher fibrinolytic and thrombolytic activity and lower fibrinogenolytic activity than urokinase.
Keywords: Plasminogen activator; Thrombolytic agent; Epithelial; Fibrinolytic enzyme